USING CHILDREN LITERATURE FOR TEACHING ACADEMIC WRITING - Lestari Setyowati; Nur Samsu (Proceedings of ISELT FBS Universitas Negeri Padang, 2015)
Almost all language teachers share typical opinions that literature is oftenly seen as complex and difficult. Thus, it is almost neglected and has not been given much emphasis in EFL classroom untill recently. Many EFL teachers often wonder how to utilize literary works in their teaching of language. Used appropriately and chosen carefully, some literary works, especially children literature, can work very well in ELT classroom, especially in writing class. The paper is aimed at sharing some knowledge on the characteristics of children literature, the characteristics of academic writing, what types of children literature that can be used in ELT writing class, and how to use those literary works for teaching that fit into the academic writing class. There are three stages that should be taken to use literary work to teach writing: a warmer stage, prewriting stage, and the writing stage. In the warmer stage, the learners are made ready for the topic through discussions about the works, such as about the writer and their prior knou,ledge of the work. In the prewriting stage, they are exposed to the work either by audio visual media or paper-based material, followed with a short discussion about the work. Finally, in the writing stage, they are given to write about their opinion in relation to the poem or short story presented earlier. using literary works for teaching writing for adult learners enhances not only the their writing ability but also their critical thinking.